Colonization of Toxigenic Clostridium difficile Among Intensive Care Unit Patients: A Multi-Centre Cross-Sectional Study - Mi, Hongfei; Bao, Rong; Xiao, Yao; Cui, Yangwen; Sun, Wei; Shen, Yan; Shi, Qingfeng; Chen, Xiang; Lin, Jiabing; Hu, Bijie; Gao, Xiaodong (Frontiers in Cellular and Infection Microbiology, 2020)
Background: Clostridium difficile (CD) is a major cause of healthcare-associated infections and antibiotic-associated diarrhoea in hospitalized patients worldwide. Carriers of toxigenic CD (tCD) have a higher risk of developing CD infections and can transmit CD to the environment and susceptible patients. However, little is known regarding the carriers and transmission of tCD in China. Methods: A multi-centre cross-sectional study of tCD colonization (tCDC) was conducted from October 24 to 31, 2014, at 33 hospitals in Shanghai, China. Rectal swabs or stool samples were collected and tested, and the clinical and demographic status, epidemiological data, and blood parameters of 531 participants were recorded. The status of tCDC was defined by a positive result on the nucleic acid amplification test for the tcdA (toxin A), tcdB (toxin B) and cdtAB (toxin CDT) genes after positive bacterial culture. Results: The overall prevalence of CD colonization (CDC) was 19.02%, tCDC accounted for 92.08%, and A+B+CDT- was the dominant genotype (87.13%). The CD infection (CDI) prevalence was 1.51%. Potential tCDC-associated factors were admission to secondary grade hospitals, a body mass index <18.5, hospitalization during the previous 30 days, underlying diseases (including hypertension, diabetes mellitus, coronary heart disease, and respiratory failure), diarrhoea during the previous 7 days, and exposure to fluoroquinolones or lansoprazole). Conclusions: This study reveals the prevalence of CDC and tCDC in Shanghai, elucidates several associated factors, contributes to the awareness of the current epidemiology in parts of eastern China and provides new insights for further study and infection control practices.